Rola sportu w promocji miast - Smura, Marcin (Wydawnictwo Naukowe WNPiD UAM, Poznań, 2012)
Duże imprezy sportowej, takie jak UEFA EURO 2012, stanowią również szansę na promocję dla miast goszczących tego typu wydarzenia. Dotyczy to nie tylko piłki nożnej ale również innych popularnych dyscyplin sportowych. Artykuł zawiera szereg przykładów tego jak poszczególne miasta wykorzystały szansę promocyjną jaką dały im duże wydarzenia sportowe. Podejmuje również próbę oceny efektywności tego typu działań. Big sporting events such as UEFA EURO 2012 are an excellent opportunity not only to compete on the pitch, but also to promote the host city. It applies to football and some other popular sports as well. It seems to be the chance to create the city’s image owing to the fact that the city organizes the event, supports players and prepares advertising campaigns. The article shows some examples how cities take advantage of such sporting events. What is more, the article aims at evaluating the effectiveness of such actions.
The Role of Sport in the City Promotion
Keywords: sport; promocja miast; euro